Ecoparque humedal El Burro (2022)
Due to the growth of the cities, the natural heritage of the wetlands has been affected, because the cities are absorbing them, which has generated a strong decrease in their hectares, losing in turn the heritage of flora and fauna. In this research, the problems of the El Burro wetland natural heritage in Bogotá Colombia are investigated, in this way it is concluded that an interaction between the neighboring community and the wetland is necessary, in order to protect this territory more, managing to establish limits , so that the wetland continues with its function avoiding floods, protecting its fauna and flora.